POLA HUBUNGAN PATRON-CLIENT DAN STRATEGI PENGEMBANGAN GAPOKDAKAN (GABUNGAN KELOMPOK BUDIDAYA IKAN) DI DESA TAMBAK REJO, KECAMATAN PADANG JAYA KABUPATEN BENGKULU UTARA - Nugraha, Yan Yan S.; Badrudin, Redy; Utama, Satria Putra (Jurnal AGRISEP, 2017)
The research aims to identify patterns of relationships patron-client in Tambak RejoVillage, to analyze internal and exsternal factors which is an aspect of theopportunities, threats, strengths and weaknesses in the development Gapokdakan in Tambak Rejo Village, Formulating alternative development strategies Gapokdakan in Tambak Rejo Village. The type of data used are primary and secondary data. Primary data were obtained by direct observation and interviews in depth about gapokdakan  and secondary data from the literature books, articles, court documentation etc. The analytical method used is descriptive analysis to determine the pattern of patronclient, a SWOT analysis to look at the search for and review of internal and external factors to determine a good decision, whereas for determining the position of developmental conditions Gapokdakan that the formulation matrix IFE (Internal Factor Evaluation ) and matrix EFE (External Factor Evaluation). The results of this research is the patron-client that occurred in the Tambak Rejo village is lending system capital provided by middlemen to farmers in the form of fish feed, but this kind of relationship there are times when farmers in disadvantaged because of the incompatibility of fish price per kilogram, and the price increase feed if borrowed from brokers, on the other hand the benefits that the convenience of farmers to capital, marketing is assured, and farmers can continue farming fish. SWOT analysis for the IFE and EFE matrix is internal factor the highest strength is the availability of the fish pond, the highest weaknesses are internal factors that are difficult or capital financing farmers, the results of internal factors evaluation matrix, internal factor of gapokdakan is good. External factors greatest opportunities, namely the potential of tilapia hatchery in the Tambak Rejo village, as well as external factors are the biggest threat is the virus tilapia. There are two alternative development strategies Gapokdakan in Tambak Rejo, one of the strategic alternatives that Increase production with facilities and infrastructure and maintain the quality so that production can always meet existing market. Keywords: Patron-Klien, Swot, strategic alternative, Gapokdakan